Development of an E-Booklet Utilizing Endophytic Fungi Isolated from Phalaenopsis amabilis Roots to Enhance Learning Outcomes on Kingdom Fungi Material - Sri Wulandari; Dwi Sucianingtyas Sukamto; Hanif Rafika Putri (Universitas Pendidikan Mandalika, 2025)
This study aims to develop an E-Booklet utilizing endophytic fungi isolated from the roots of Phalaenopsis amabilis to improve learning outcomes of Kingdom Fungi material for class X MA Zainul Bahar students, Bondowoso. The research method used is the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The isolation results show a diversity of endophytic fungi that are potentially authentic learning resources. This e-booklet is organized in an interactive and contextual manner, integrating isolation result data into teaching materials that are in accordance with the Merdeka Curriculum. The novelty of this research lies in the utilization of endophytic fungi from the roots of P. amabilis as a source of local content that has not been widely explored in learning media. In addition, the use of the E-Booklet format based on original research data provides added value in the form of a scientific approach directly from the field, which is not yet available in conventional learning resources. This study involved 27 grade X students using the one-group pretest-posttest design method and an expert validation test. Validation by experts gave the material a score of 91% (very valid) and media 87% (very valid), while the practicality test based on student questionnaires reached 85% (practical). N-gain analysis of 0.82 (high category) shows that this E-Booklet effectively improves students' learning outcomes on the Kingdom Fungi material.